“A diamond-shaped” penoplasty technique with or without concurrent suprapubic liposuction for adult-acquired buried penis: clinical outcomes and patient satisfaction rates - Jing Wang; Jian Ni; Yang Xu; Wen Yu; Zhi-Peng Xu; Yu-Tian Dai; Yi-Qiong Yang; Xiao-Zhi Zhao (Asian Journal of Andrology, 2025)
Various techniques have been described for reconstructing the skin of the penile shaft; however, no universally accepted standard exists for correcting buried penis in adults. We aimed to describe a new technique for correcting an adult-acquired buried penis through a diamond-shaped incision at the penopubic junction. We retrospectively analyzed data from patients treated with our technique between March 2019 and June 2023 in the Department of Andrology, Nanjing Drum Tower Hospital (Nanjing, China). Forty-two adult males with buried penises, with a mean (±standard deviation [s.d.]) age of 26.6 (±6.6) years, underwent surgery. All patients were obese, with an average (±s.d.) body mass index of 35.56 (±3.23) kg m−2. In addition to phalloplasty, 32 patients concurrently underwent circumcision, and 28 underwent suprapubic liposuction. The mean (±s.d.) duration of the operation was 98.02 (±13.28) min. The mean (±s.d.) duration of follow-up was 6.71 (±3.43) months. The length in the flaccid unstretched state postoperatively was significantly greater than that preoperatively (mean ± s.d: 5.55±1.19 cm vs 1.94±0.59 cm, P < 0.01). Only minor complications, such as wound disruption (7.1%) and infection (4.8%), were observed. The mean (±s.d.) score of patient satisfaction was 4.02 (±0.84) on a scale of 5. This technique provides excellent cosmetic and functional outcomes with a minimal risk of complications. However, additional clinical studies are needed to evaluate the long-term effects of this procedure.